The Role of Dietary Fiber in Gastrointestinal Health: Focus on Irritable Bowel Syndrome and Diverticular Disease - Kapler, Marta; Kotula, Jacek; Mąsior, Magdalena Natalia; Zinkow, Karolina; Gawlik, Łukasz Marek (Quality in Sport, 2024)
Dietary fiber (DF) encompasses a variety of plant-derived carbohydrates resistant to human digestive enzymes, significantly influencing gastrointestinal health. This study examines the role of DF in managing Irritable Bowel Syndrome (IBS) and Diverticular Disease (DD), utilizing comprehensive analysis from PubMed, Google Scholar, and Embase. IBS, affecting 10-20% globally, involves complex brain-gut interactions, motility issues, and microbiota changes. Soluble fiber like psyllium reduces IBS symptoms by improving stool consistency and regulating bowel movements. However, the role of DF in DD is more nuanced. While the reports on the impact on diverticulosis prevalence are contradictory, numerous moderate-quality studies confirmed the protective effect against recurrent diverticulitis and hospitalization. The effect of different fiber types on this matter was not widely explored which might explain the discordances between the studies. Further research is essential to fully understand the diverse effects of different types of DF on gastrointestinal (GI) health. This way, exhaustive guidelines specific to each fiber type and disease phenotype could be developed, allowing to tailor the dietary recommendations to each patient, optimizing the management of symptoms of IBS and DD, and improving the quality of life.